A Systematic Investigation on Complement Pathway Activation in Diabetic Retinopathy - Shahulhameed, Shahna; Vishwakarma, Sushma; Chhablani, Jay; Tyagi, Mudit; Pappuru, Rajeev R.; Jakati, Saumya; Chakrabarti, Subhabrata; Kaur, Inderjeet (Frontiers in Immunology, 2020)
The complement system plays a crucial role in retinal homeostasis. While the proteomic analysis of ocular tissues in diabetic retinopathy (DR)has shown the deposition of complement proteinstheir exact role in the pathogenesis of DR is yet unclear. We performed a detailed investigation on the role of complement system by evaluating the levels of major complement proteins including C3, C1q, C4b, Complement FactorB (CFB) and Complement Factor H (CFH)and their activated fragments from both the classical and alternative pathways in vitreous humor and serum samples from proliferative DR (PDR) patients and controls. Further, the expressions of complements and several other key pro and anti-angiogenic genes in the serum and vitreous humor were analyzed in the blood samples of PDR, non-PDR (NPDR) patients along with controls without diabetes. We also assessed the proinflammatory cytokines and matrix metalloproteinases in the vitreous humor samples.There was a significant increase in C3, its activated fragment C3bα’ (110kDa) along with a corresponding upregulation of CFHin the vitreous of PDR patients that confirmed the increased activation of alternative complement pathway in PDR. Likewise, a significant upregulation of angiogenic genes and down regulation of anti-angiogenic genes was seen in PDR and NPDR cases. An increased MMP9 activity and upregulation of inflammatory markers IL8, sPECAM with a down regulation of anti-inflammatory marker IL-10 in PDR vitreous indicated the possible involvement of microglia in DR pathogenesis. Further,a significantly highC3 deposition in the capillary wall alongwith thickening of basement membranes and co-localization of CFH expression with CD11b+ve activated microglial cells in diabetic retina suggested microglia as a source of CFH in diabetic retina.Theincreased CFH levels could be a feedback mechanism for arresting excessive complement activation in DR eyes. A gradual increase ofCFHand CD11bexpression in retina with early to late changes in epiretinal membranes of DR patients indicated for a major role of alternate complement pathway in disease progression.